ICE manual of geotechnical engineering. - Brown, Michael; Burland, John; Chapman, Tim; Higgins, Kelvin; Skinner, Hilary; Toll, David ([ICE manuals], 2023)
ICE Manual of Geotechnical Engineering, Second edition brings together an exceptional breadth of material to provide a definitive reference on geotechnical engineering solutions. Written and edited by leading specialists, now revised and updated with the latest guidelines and references, each chapter provides contemporary guidance and best practice knowledge for civil and structural engineers in the field. It considers the higher importance attached to the effects of construction on the environment and society. Key features in this wide-ranging update include * comprehensive reference for the core geotechnical engineering principles * theoretical principles and practical techniques in geotechnical engineering * uncertainties that may arise during the process of ground investigation * topic-focused chapters, including problematic soils, foundations, earthworks and retaining structures * fundamental principles of site investigation, design and construction processes. Volume II covers design of foundations, retaining structures and earthworks, slopes and pavements, construction processes and verification.This volume uses and builds on the principles and concepts, problematic soils and site investigation detail covered in Volume I. Part of the ICE Manuals series, ICE Manual of Geotechnical Engineering, Second edition is an essential guide and invaluable reference for practising civil and structural engineers, engineering geologists, architects, designers, consultants and contractors.